A Poetics of Neurosis Narratives of Normalcy and Disorder in Cultural and Literary Texts - Furlanetto, Elena; Meinel, Dietmar (Edition Kulturwissenschaft, 2018)
While psychiatry and the neurosciences have dismissed the concept of neurosis as too vague for medical purposes, in recent years literary studies have adopted the term by virtue of its abstractness. This volume investigates the verbalization of neurosis in literary and cultural texts. As opposed to the medical diagnostics of neurosis in the individual, the contributions focus on the poetics of neurosis. They indicate how neuroses are still routinely romanticized or vilified, bent to suit aesthetic and narrative choices, and transfigured to illustrate unresolved cultural tensions.